2015
DOI: 10.3109/0886022x.2014.996088
|View full text |Cite
|
Sign up to set email alerts
|

Stroke-free status and depression scores among Saudi dialysis patients

Abstract: Background: To assess the prevalence of stroke symptoms and depression among Saudi dialysis patients and related factors. Methods: This is a cross-sectional multicentre study of Saudi dialysis patients. Demographics, clinical and laboratory's data were collected. Freedom from stroke symptoms was assessed using the Questionnaire for Verifying Stroke-Free Status and depression using the Geriatric Depression Scale. Results: Five-hundred and forty-nine patients (77.3% response rate); 94.6% were receiving hemodialy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In a multicenter explorative investigation of dialysis patients in Saudi Arabia, Sheayria et al . [ 36 ] found that 45.2% of the elderly dialysis patients have mild depressive symptoms and 6.1% have major depression. This is higher than the 20% figure for depression prevalence among dialysis patients found in international studies.…”
Section: Discussionmentioning
confidence: 99%
“…In a multicenter explorative investigation of dialysis patients in Saudi Arabia, Sheayria et al . [ 36 ] found that 45.2% of the elderly dialysis patients have mild depressive symptoms and 6.1% have major depression. This is higher than the 20% figure for depression prevalence among dialysis patients found in international studies.…”
Section: Discussionmentioning
confidence: 99%